Towards Green Campuses: Students’xx Perceptions and Expectations - Tezel, Ecem; Giritli, Fatma Heyecan; UĞURAL, MEHMET NURETTİN (My University, 2018)
The contribution of education to sustainable development has been emphasized many times by education professional, researchers and global leaders. Hence, strategies for quality education were placed among UN Sustainable Development Goals for 2030. In order to ensure effective learning of sustainability, building and upgrading education facilities is as important as teaching of it. Green campus concept, in this scope, is expected to provide a medium to enhance the awareness of students about environment and contribute to their theoretical knowledge about sustainability through practical implementations. Numerous higher education institutions are recently adapting their facilities according to environmentally friendly guidelines while educating their students about environment and sustainability subjects. The purpose of this study is to understand the influence of education on students’ perceptions about sustainability and determine the expectations of students in terms of green campus implementations. In addition to investigate the prevalent green campus practices worldwide, this study analyzes the relationship between students’ perceptions about sustainability field and level of sustainability education taken during higher education. Results of the study highlight important perception and expectation differences between international and Turkish students.
Keywords: expectation; green campus; perception; students; sustainability in higher education